What are the prospects of the Yuan becoming the World’s new Reserve Currency? - Garić, Danko; Filipovic, Sanja (Industrija, 2019)
China has long been the world’s second largest economy, with the largest foreign exchange reserves and the second largest share in world trade. However, its position in the global economy has long been recognized, but this recognition has not been accompanied by the international monetary significance of the yuan. Despite China’s economic significance, the political importance and the voting power in the International Monetary Fund (IMF) cannot be compared to that of the U.S. because the U.S. has over 17% of the votes, whereas China has 3.8 %. Owing to that, the U.S., together with its allies, gets to block decisions and tailor global economic policy. Striving to establish the world’s reserve currency, China has been leading comprehensive economic and trade policies while strengthening the yuan convertibility. As a result, effective October 1, 2016, the yuan has become a reserve currency in the basket of special drawing rights along with the dollar, the euro, the yen, and the British pound. China has been supporting the IMF reform while establishing new institutions aimed at redefining the current international policy under the strong influence of the U.S. The paper analyses the channels of Chinese authorities’ actions and the prospect of recomposing the international monetary system and reducing the global U.S. influence, with the aim of identifying whether it is likely that the Chinese currency will obtain the status of the world currency.